A problematic cnidarian (Cambroctoconus; Octocorallia?) from the Cambrian (Series 2–3) of Laurentia. (9th August 2017) - Peel, John S.
Abstract: The problematic calcified cnidarian Cambroctoconus is described from the Henson Gletscher Formation (Cambrian Series 2, Stage 4–Series 3, Stage 5) of North Greenland, representing the first record from Laurentia of a genus otherwise recently described from China, Kyrgyzstan, and Korea. Internal molds produced by penetrative phosphatization mirror the pervasive pore system of the calice walls and septa. The pore system is compared to the network of gastrodermal solenia that distributes nutrients between polyps and surrounding stolon tissues in present day octocorals. In conjunction with the octagonal form of the individual coralla and eight-fold symmetry of septa, the pore system promotes assignment of Cambroctoconus to the Octocorallia, a basal clade in cnidarian phylogeny. Octocorals ('soft corals') are diverse in present day seas, but have a poor fossil record despite the general development of distinctive calcareous spicules. New taxa: Order Cambroctoconida new; Cambroctoconus koori new species.